Empowering Students’ 21st Century Skills through Canva Application - Anastasia Dewi Anggraeni; Helda Jolanda Pentury (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The study aimed at investigating the use of Canva platform as digital media in writing lesson to empower students’ 21st skills. The qualitative-descriptive method is used in this study. The research subject was 60 students at Indraprastra PGRI Jakarta University, majoring in English Education who were given questionnaires, feedback and observed by their projects to collect the data. The results showed that most of the students 21st century skills empowered well in writing through various project templates in Canva platform. It was concluded that Canva carried out more effectively, not only students will produce good projects, but their core competencies in writing can also be broadened and strengthened. Moreover, using appropriate media, projects, authentic topics and students’ feedbacks can empower students to be critical thinker, creator, communicator and collaborator as well in academic and beyond.